PENINGKATAN NILAI GIZI PRODUK PANGAN DENGAN PENAMBAHAN BUBUK DAUN KELOR (Moringa oleifera): REVIEW - Clarita Angelina; Yuliana Reni Swasti; Franciscus Sinung Pranata (Faculty of Agricultural Technology, University of Jember, 2021)
In several countries, moringa leaves are starting to be widely used in food products as an alternative to overcome malnutrition. Malnutrition occurs due to a lack of energy and protein balance which disrupt human physiological function. The lack of micronutrient intakes, such as vitamin A, iron, and zinc, can also cause malnutrition. Moringa oleifera is referred to as the most economical tree. Almost every part of the tree contains abundant nutrients and plays an important role in meeting human nutritional needs. Moringa leaves contain high protein, vitamins, and minerals, to be used as an alternative to overcome nutritional problems. Various studies have concluded that moringa leaves can be used in food products. This review aims to determine the use of moringa leaves to increase the nutritional content in food products. The addition of moringa leaf powder causes a significant increase in protein, fiber, and mineral content in several food products. The addition of moringa leaf powder with the highest concentration resulted in the best increase in protein, fat, fiber, and mineral content in several food products. However, the acceptable concentration of moringa leaf powder addition is not more than 5%. Keywords: mineral content, moringa leaf, nutrient